Exploring the reading strategies exploited by better readers / Noli Maishara Nordin, Roslan Sadjirin and Roselina Musahar - Nordin, Noli Maishara; Sadjirin, Roslan; Musahar, Roselina (2013)
Students' level of understanding in reading depends much on the use of appropriate strategies during the activity. The strategies not only affect students' comprehension of the text, but also determine their academic achievement. This study aimed to investigate the reading strategies used by English as a Second Language (ESL) high achievers at tertiary level. Specifically, it aimed to identify the reading strategies frequently used by the respective ESL learners. Additionally, it aimed to find out whether there was any significant different in the type of strategies used by ESL high achievers? Forty undergraduate students were randomly selected as the respondents for this study. A twenty-eight-item questionnaire, which focused on the frequency of use of pre, while, and post-reading strategies was utilised in the study. It was found that ESL high achievers frequently used certain reading strategies to grasp the meaning of the text. The ESL high achievers were also reported to significantly use post-reading strategies as their distinctive remark. The findings suggest that the use of appropriate reading strategies should be exposed to students to help them enhance their comprehension of a reading text and make them become better readers.